PENGARUH MOTIVASI MATERIAL DAN MOTIVASI NON MATERIAL TERHADAP SEMANGAT KERJA KARYAWAN DI PT DAYA ADICIPTA SANDIKA - Sumarsid, Sumarsid (Feb Universitas Dirgantara Marsekal Suryadarma, 2017)
In the analysis of these data, the authors collected data that can support research by distributing questionnaires to 35 respondents from all employees of Sales at PT Daya Adicipta Sandika, with the results of the study are: The results of the analysis of the correlation coefficient obtained correlation coefficient value X1 Motivation Materials on Employee Morale was 0.630, and the correlation coefficient X2 Motivation Non Material to Employee Morale was 0.588, thus the motivation Material and Motivation Non Material has strong relationships and significant (0.000 <0 , 05) of the Employee Morale PT Daya Adicipta Sandika. The results of the analysis obtained value of the coefficient of determination (R2) = 0.529, thus variables X1 (Motivation Material) and X2 (motivation Non Material) contributed 52.9% to variable Y (Employee Morale) in PT Daya Adicipta Sandika and the rest by 47.1% influence of other factors that are not the authors studied, for example, the influence of the leadership, work stress, and cooperative relationships between employees. Furthermore, the research hypothesis testing that digunakann by F test (simultaneous) showed that the significant value of the variable X1 is motivation motivational material and nonmaterial X2 is 0.000> 5% (0.000> 0.05), so Ho rejected and Ha accepted , meaning that simultaneously seek material and non-material motivation significant effect on employee morale at PT Daya Adicipta Sandika. Similarly, through the t test (partial) obtained significant value for the variable X1 Material Motivational 0,001 <5% (0.001 <0.05) and a significant value for the variable X2 Non Material Motivation of 0.005 <5% (0.005 <0.05 ), and thus Ha (alternative hypothesis) is received and Ho (null hypothesis) is rejected. Meaning and Motivation Motivation Material Material Non partially significant effect on Morale Employees at PT Daya Adicipta Sandika. Furthermore, the company provides compensation to employees who adapted the work performance and in early stages of the fair as a motivation that is material to boost employee morale, and should the Company give appreciation to employees who have been achieving, by giving awards for example in the form of an opportunity to develop themselves so that employees are encouraged to work harder. Keywords: Motivation Material, Non Material Motivation and Morale